STRUKTUR MODAL SEBAGAI VARIABEL MODERASI PENGARUH LIKUIDITAS DAN PROFIBILITAS TERHADAP FIRM VALUE: (Studi Kasus Pada Perusahaan Perbankan di BEI Tahun 2016-2019) - Irma Indira; Eva Wany (Media Mahardhika, 2021)
This research aims to conduct testing as well as know the capital structure moderating the influence of liquidity and profitability on firm vaue. The place where this research was conducted is in IDX where it uses the banking sector. The samples used in this study used purposive sampling method with samples of 96 companies from 2016 to 2019. In research studies the use of methods is used to explain the relationship and influence on variables using multiple analysts. The results of this study have proven the results if liquidity has a negative and significant impact on the firm value,while profitability has a positive impact on the firm value. The capital structure is able to moderate liquidity in firm value but does not moderate the influence of prifitability on firm value.